Perioperative application of dexmedetomidine for postoperative systemic inflammatory response syndrome in patients undergoing percutaneous nephrolithotomy lithotripsy: results of a randomised controlled trial. Issue 11 (3rd November 2018) - Deng, Yingqing; Tan, Fang; Gan, Xiaoliang; Li, Xiaoyun; Ge, Mian; Gong, Chulian; Hei, Ziqing; Zhu, Qianqian; Zhou, Shaoli
Abstract : Objective: Our previous retrospective study demonstrated that perioperative dexmedetomidine (Dex) administration was associated with low systemic inflammatory response syndrome (SIRS) incidence. The present study was designed to investigate whether perioperative administration of Dex decreases the incidence of postpercutaneous nephrolithotomy lithotripsy (PCNL) SIRS in patients who undergo PCNL. Design: A randomised controlled trial was designed. Participants: A total of 190 patients were randomly assigned to receive Dex (DEX group, n=95) or saline control (CON group, n=95) and completed the study. In the DEX group, Dex was loaded (1 µg/kg) before anaesthesia induction and was infused (0.5 µg/kg/h) during surgery. Outcomes: The incidences of postoperative SIRS were recorded. Serum interleukin-6 (IL-6) and tumour necrosis factor α(TNF-α) were measured. Results: The incidence rates of SIRS were significantly lower in the DEX group than in the CON group (35.8% vs 50.5%, p=0.04). No patients developed sepsis in either group. These results might be attributed to inhibition of inflammatory responses and the resulting lower serum levels of IL-6 and TNF-α, caused by Dex administration. However, compared with the CON group, the lower incidence rate of SIRS in the DEX group did not result in better outcomes, such as shorter postoperative hospitalisation stays and lower costs. Conclusion: The present study showed that Dex administration during PCNL might be beneficial for decreasing the incidence of SIRS through inhibiting the release of inflammatory mediators, but not clinical consequences such as postoperative hospitalisation duration and costs. Further effects of Dex administration on SIRS in patients who are scheduled for PCNL should be explored in future studies. Trial registration number: ChiCTR-ICR-15006167.